Professional development in private university libraries in Ghana. Issue 6 (13th August 2018) - Dzandza, Patience Emefa; Akussah, Harry
Abstract : Purpose: There has been a significant change in the provision of library services due to the application of technology to every aspect of library services. This has posed a major challenge to library staff as they need to be abreast with current technologies and their application to library services. One means by which a librarian can overcome this challenge is through professional development (PD) programs. The purpose of this paper is to determine PD opportunities in private university libraries in Ghana. Design/methodology/approach: A cross-sectional survey of 61 staff and interviews with 20 heads of libraries was conducted to collect data from 25 private universities in Ghana. Findings: The study revealed that not all library staff in the private universities were allowed to attend PD programs. None of the private universities studied had a policy on PD and only three institutions made budgetary allocation to PD programs. Majority of the private universities did not have in-house PD programs and there were no means of knowledge sharing in most of the libraries studied. Originality/value: In this paper, the researchers identified the major challenges encountered by library staff in private universities in Ghana and propose that librarians should see PD as a part of their own responsibility while, libraries should have a PD policy and make budgetary allocation toward PD.